PENGEMBANGAN PERANGKAT PENGAJARAN MATEMATIKA DENGAN PENDEKATAN PMR BERBANTUAN CD INTERAKTIF PADA MATERI PERSAMAAN LINEAR SATU VARIABEL KELAS VII - Zaenal Mutaqin, Ikin (Universitas Wiralodra, 2016)
This study aimed to develop and produce devices PMR mathematics learning approach aided interactive CD on the material linear equations class VII are valid and effective. The result of the development of mathematics learning with PMR approach on the material linear equations of one variable of class VII shows the validation results of the experts. Implementation field learning device that has generated valid and effective tool with active variable and process skills, reaching thoroughly studied, the effect of active variable and process skills to the learning outcomes and no difference between the control group and the implementation class. Once implemented obtained that result is students achieve a complete study with KKM = 65 gained 79.8 completeness. There is an active variable and process skills influence on the process of student learning outcomes by 79.3%. There are differences between the control group (66.7) and the implementation class (78.0). It concluded that the study of mathematics by PMR approach aided interactive CD on material class VII PLSV valid and effective.